Normative uncertainty and societal preferences: the problem with evaluative standards - Kuilman, Sietze Kai; Andriamahery, Koji; Jonker, Catholijn M.; Siebert, Luciano Cavalcante (Frontiers in Neuroergonomics, 2023)
More and more technological systems interact with their environment with less human intervention. This comes with higher stakes and consequences that society needs to manage. No longer are we dealing with 404 pages, AI systems today may cause serious harm. To address this, we desire a kind of control over these systems, so that they can adhere to our moral beliefs. However, given the plurality of values in our societies, which `oughts' do these machines ought to adhere to? In this paper, we take a look at Borda voting as a way to maximize expected choice-worthiness between individuals through different possible ``implementations'' of ethical principles. We use the moral machine experiment data to visualize the effectiveness of such a voting. It proves to be effective, although maximizing expected choice-worthiness is very dependent on the formulation of credences. The capacity for such formulations is notoriously hard, hence such mechanisms should be taken with caution in real-world implementations, favouring socio-technical approaches that support meaningful human control.